Changes in patient-reported chief complaints with orthognathic surgery: a prospective cohort study - Lennart Stadtmann; Moritz Kanemeier; Thomas Stamm; Claudius Middelberg; Carolien A. J. Bauer; Johannes Kleinheinz; Jonas Q. Schmid (Progress in Orthodontics)
Abstract Objective There is a lack of studies on patient-reported outcomes in orthodontics. The aim of this study was to evaluate the changes in patient-reported chief complaints during orthognathic surgery treatment. Materials and methods Patients undergoing orthognathic surgery at the University Hospital Münster between 2019 and 2023 were eligible for inclusion in this prospective cohort study. Patient-reported chief complaints were recorded on visual analogue scale (VAS) forms before treatment ( $$\text {T}_{0}$$ ), and reevaluated after presurgical orthodontic treatment ( $$\text {T}_{1}$$ ), and 6–9 months after surgery ( $$\text {T}_{2}$$ ). Chief complaints were grouped into three main categories (pain, function, aesthetics) and ten subcategories, and their intensity was quantified over time. Results A total of 217 out of 386 recruited patients (56%) completed all study assessments and were included in the final analysis (female/male = 126/91, median age 24.1 years). Dental function, facial aesthetics, and dental aesthetics were the most frequently reported complaints at $$\text {T}_{0}$$ . At $$\text {T}_{1}$$ , there was a statistically significant improvement in dental aesthetics. There was a statistically significant reduction in the intensity of each of the 10 subcategories from $$\text {T}_{0}$$ to $$\text {T}_{2}$$ . Conclusion Orthognathic surgery patients most frequently report dental function, facial aesthetics, and dental aesthetics as their chief complaints, and these complaints were improved significantly after treatment. Clinical relevance The improvement in patient-reported chief complaints can be used to inform patients prior to treatment.